(untitled) (Neo Science Peer Reviewed Journal, 2023)
Infectious diseases arose long before the appearance of man. There are traces of osteomyelitis on the bones of dinosaurs, mammoths, cave bears and other ancient animals. Of the human ancestors, infectious bone lesions were noted in pithecanthropes from the island of Java, who lived 1-2 million years ago. Thus, mankind at the dawn of its existence met with numerous infectious diseases. Obviously, in terms of quantity, total mass, reproduction rate and duration of existence on Earth, bacteria absolutely surpass humans. That is why, as society emerged and the social way of life of a person developed, many infections became widespread. In general, three historical stages of the relationship between mankind and infections can be distinguished.